The Influence of Transformational Leadership Skills and Organizational Climate on Job Satisfaction Which Impact Business Performance - Ni Luh Yulyana Dewi; I Wayan Joniarta; Ni Ketut Arniti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to determine the Effect of Transformational Leadership Skills and Organizational Climate on Job Satisfaction which Impact Business Performance at PT. Inti Jaya Purnama, Central Jakarta, DKI Jakarta. In this study using a type of quantitative research with a survey approach with the method used is simple random sampling, with a sample of 155 employees. The data analysis technique of this research uses PLS software version 3.0 (Partial Least Square) which is a variant-based structural equation model that can simultaneously test the measurement model as well as test the structural model with the research results obtained that 1) Transformational Leadership Skills on job satisfaction with a t-statistic value of 10.035 > t-table 1.975 and a P-value of 0.000 > 0.05, 2) Organizational Climate has a positive and significant effect on job satisfaction with a t-statistic value of 4.955 > t -table 1.975 and a P-value of 0.000 <0. 05, and 3) job satisfaction has an effect on Business Performance with at statistical value of 22.687 > t table of 1.975 and a P-value of 0.000 <0.05.